Composite bone repair material and preparation method thereof

By combining amorphous calcium phosphate copper nanomaterial with polymer materials and using 3D printing technology to prepare composite bone repair materials, the problem of infection after implantation of existing bone repair materials is solved, and both antibacterial performance and osteogenic activity are achieved.

CN119868660APending Publication Date: 2025-04-25INST OF METAL RESEARCH - CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510015539.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing bone repair materials are prone to infection after implantation, and are difficult to have both antibacterial properties and osteogenic activity.

Method used

Combination of amorphous calcium phosphate copper nanomaterial and polymer materials is used to prepare composite bone repair materials through mixing treatment and 3D printing technology, and calcium ions are used to promote bone tissue regeneration and copper ions are significantly antibacterial.

Benefits of technology

The antibacterial properties and osteogenic activity of composite bone repair materials are achieved, the problem of post-implantation infection is solved, and good mechanical properties and biodegradability are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868660A_ABST
    Figure CN119868660A_ABST
Patent Text Reader

Abstract

The invention provides a composite bone repair material and a preparation method thereof, and relates to the field of additive manufacturing bone tissue repair materials.The preparation method comprises the following steps that 1, an amorphous copper calcium phosphate nanometer material and a substrate material solution are mixed, and a substrate / amorphous copper calcium phosphate composite material is obtained; wherein the substrate material is a high polymer material; the preparation method comprises the following steps: mixing an amorphous copper calcium phosphate nano material with a solution of a substrate material to obtain a substrate / amorphous copper calcium phosphate composite material, and preparing the substrate / amorphous copper calcium phosphate composite material into the composite bone repair material. Wherein calcium ions in the amorphous copper calcium phosphate nano material are beneficial to promoting bone tissue regeneration, and copper ions have remarkable antibacterial performance, so that the obtained composite bone repair material has osteogenesis and antibacterial performance, and the problems of infection and the like after an existing clinical bone repair material is implanted are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of additive manufacturing of bone tissue repair materials, and specifically relates to a composite bone repair material and a preparation method thereof. Background Art

[0002] In clinical practice, infection after bone defect repair is a common and serious problem, which can lead to delayed wound healing and tissue dysfunction. Bacterial infection not only affects the patient's recovery process, but may also cause more serious complications such as osteomyelitis and infectious arthritis.

[0003] The prior art has disclosed bone repair materials prepared by doping polymer materials with nanomaterials, and calcium ions can be used to make the bone repair materials have osteogenic activity. However, the bone repair materials are difficult to solve the problems of infection after implantation of clinical bone repair materials.

[0004] In view of this, it is necessary to provide a composite bone repair material that has both antibacterial properties and osteogenic activity. Summary of the invention

[0005] Therefore, the present invention provides a composite bone repair material and a preparation method thereof, the main purpose of which is to provide a composite bone repair material having both antibacterial properties and osteogenic activity.

[0006] In order to solve the above problems, the present invention provides a method for preparing a composite bone repair material, comprising the following steps:

[0007] Step 1): mixing an amorphous calcium copper phosphate nanomaterial with a solution of a substrate material to obtain a substrate / amorphous calcium copper phosphate composite material; wherein the substrate material is a polymer material;

[0008] Step 2): preparing the substrate / amorphous calcium phosphate copper composite material into a composite bone repair material.

[0009] Further, in the step 1):

[0010] The particle size of the amorphous calcium copper phosphate nanomaterial is 20-100 nm; and / or

[0011] The mass percentage of Cu element in the amorphous calcium phosphate copper nanomaterial is 0.1-20%.

[0012] Furthermore, the preparation steps of the amorphous calcium copper phosphate nanomaterial include:

[0013] Step S1): mixing a mixed solution A containing a calcium inorganic salt, a copper inorganic salt and polyacrylic acid with a mixed solution B containing a phosphate and polyacrylic acid to obtain an emulsion;

[0014] Step S2): centrifuging the emulsion to obtain a precipitate;

[0015] Step S3): post-treating the precipitate to obtain amorphous calcium copper phosphate nanomaterial.

[0016] Further, in the step S1), the calcium inorganic salt is calcium chloride dihydrate CaCl2·2H2O; the copper inorganic salt is copper chloride dihydrate CuCl2·2H2O; and / or

[0017] The molecular weight of the polyacrylic acid is greater than 1000; and / or

[0018] In the mixed solution A, the concentration of the calcium inorganic salt is 10-100 g / L, the concentration of the copper inorganic salt is 0.1-2 g / L, and the concentration of the polyacrylic acid is 0.5-5 g / L; and / or

[0019] The phosphate is diammonium phosphate; and / or

[0020] The mixed solution B is a mixed solution after the pH value is adjusted with aqueous ammonia; and / or

[0021] The pH value of the mixed solution B is 7-10; and / or

[0022] In the mixed solution B, the concentration of the phosphate is 1-25 g / L, and the concentration of the polyacrylic acid is 0.5-5 g / L; and / or

[0023] The mixing treatment comprises: adding the mixed solution A dropwise to the mixed solution B under stirring; preferably, the dropping speed is 1-50 mL / min; preferably, the stirring speed is 200-1000 rpm; further preferably, 400-500 rpm; further preferably, 20-25 mL / min; preferably, the stirring time is 0.5-3 h; further preferably, 2-2.5 h.

[0024] Further, in step S2), the rotation speed of the centrifugal treatment is 5000-10000 rpm; preferably 7000-9000 rpm; and / or

[0025] In step S2), the centrifugal treatment time is 3-15 min; preferably 4-6 min; and / or

[0026] In the step S3), the post-treatment step includes: washing and drying the precipitate in sequence; preferably, the washing method is dialysis washing; preferably, the drying method is freeze drying.

[0027] Furthermore, in the step 1), the solution of the base material is prepared by the following preparation method:

[0028] Dissolving a polymer material in an organic solvent to obtain a solution of the base material; wherein the polymer material comprises polylactic acid and polycaprolactone; and / or

[0029] When the amorphous calcium copper phosphate nano material is mixed with a solution of a base material, the mass fraction of the amorphous calcium copper phosphate nano material is less than 30%.

[0030] Further, in the solution of the base material: the concentration of polylactic acid is 5-50 g / L; the concentration of polycaprolactone is 50-100 g / L; and / or

[0031] Dissolving the polymer material in the organic solvent comprises: adding the polymer material to the organic solvent at a set temperature and stirring at the same time; preferably, the set temperature is 20-50°C; more preferably, the set temperature is 30-40°C; preferably, the stirring speed is 200-1000rpm; more preferably, the stirring speed is 400-500rpm; preferably, the stirring time is 1-3h; and / or

[0032] In the polymer material, the mass ratio of polylactic acid to polycaprolactone is 0.1-1:1; and / or

[0033] The number average molecular weight of the polycaprolactone is 80,000-100,000; and / or

[0034] The number average molecular weight of the polylactic acid is 60,000-80,000; and / or

[0035] The organic solvent is dichloromethane.

[0036] Further, in the step 1):

[0037] The mixing treatment comprises: adding the amorphous calcium copper phosphate nanomaterial into a solution of a base material and stirring at the same time; preferably, the stirring speed is 200-1000 rpm; further preferably, the stirring speed is 400-500 rpm; preferably, the stirring time is 6-12 hours; further preferably, the stirring time is 8-10 hours; and / or

[0038] After the mixing process, a heating process is further included; preferably, the temperature of the heating process is 40-60°C; further preferably, the temperature of the heating process is 45-55°C.

[0039] Furthermore, in the step 2), the step of preparing the substrate / amorphous calcium phosphate copper composite material into a composite bone repair material comprises: 3D printing the substrate / amorphous calcium phosphate copper composite material to obtain the composite bone repair material;

[0040] Preferably, during the 3D printing process: the printing temperature is 100-200°C; the extrusion speed is 0.05-0.5 mm / s; the moving speed of the print head is 3-10 mm / s;

[0041] Further preferably, the extrusion speed is 0.05-0.15 mm / s; and the moving speed of the print head is 6-8 mm / s.

[0042] In another aspect, the present invention provides a composite bone repair material, comprising a base material and an amorphous calcium phosphate copper nanomaterial loaded on the base material;

[0043] The elastic modulus of the composite bone repair material is greater than 90 MPa; the yield strength of the composite bone repair material is greater than 8 MPa;

[0044] Preferably, the composite bone repair material is obtained by any of the preparation methods described above.

[0045] The composite bone repair material and preparation method thereof provided by the present invention have the following beneficial effects:

[0046] 1. On the one hand, the present invention provides a method for preparing a composite bone repair material, which comprises mixing an amorphous calcium copper phosphate nanomaterial with a solution of a substrate material to obtain a substrate / amorphous calcium copper phosphate composite material, and making the substrate / amorphous calcium copper phosphate composite material into a composite bone repair material; wherein the calcium ions in the amorphous calcium copper phosphate nanomaterial help promote bone tissue regeneration, and the copper ions have significant antibacterial properties, so that the obtained composite bone repair material has both osteogenesis and antibacterial properties, thereby solving the problem of infection after implantation of existing clinical bone repair materials.

[0047] 2. Furthermore, the base material of the present invention adopts a blend of polylactic acid (PLA) and polycaprolactone (PCL), which has both the flexibility of polycaprolactone (PCL) and the mechanical strength of polylactic acid (PLA), providing good mechanical properties and biodegradability for the composite bone repair material; at the same time, using the base material of the present application, the composite bone repair material can be prepared by 3D printing, and personalized composite bones can be customized according to the specific conditions of the patient.

[0048] 3. On the other hand, the present invention provides a composite bone repair material, which is prepared by the above method, including a base material and an amorphous calcium copper phosphate nanomaterial loaded on the base material; based on the amorphous calcium copper phosphate nanomaterial, the composite bone repair material of the present invention has osteogenic and antibacterial properties, and its elastic modulus is above 90MPa, and its yield strength is above 8MPa, which can solve the problems of infection after implantation of existing clinical bone repair materials. The release of calcium ions and copper ions is controlled by the amorphous calcium copper phosphate nanomaterial, and the calcium ions help promote bone tissue regeneration, while the copper ions have significant antibacterial properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0050] Figure 1 is the XRD pattern of amorphous calcium copper phosphate (ACCP) nanomaterials prepared in Examples 1 and 6;

[0051] Figure 2 is a graph showing the ion release results of the amorphous calcium copper phosphate (ACCP) nanomaterial prepared in Example 1;

[0052] Figure 3 This is a diagram showing the antibacterial effect of amorphous calcium copper phosphate (ACCP) nanomaterial prepared in Example 1;

[0053] Wherein: (a) and (b) are respectively the graphs of bacterial solution and its 10000-fold dilution; (c) and (d) are respectively the graphs of 20 mg / mL (ACCP co-cultured with bacterial solution and its 10000-fold dilution; (e) and (f) are respectively the graphs of 10 mg / mL (ACCP co-cultured with bacterial solution and its 10000-fold dilution;

[0054] Figure 4 (a)-(c) are morphological images of the composite bone repair materials prepared in Examples 1-3, respectively;

[0055] Figure 5 is a morphological diagram of the composite bone repair material prepared in Example 4;

[0056] Figure 6 is the morphology and element distribution diagram of the composite bone repair material prepared in Example 4 under an electron microscope;

[0057] Figure 7 is a morphological diagram of the composite bone repair material prepared in Example 5;

[0058] Figure 8 The antibacterial effect diagram of the amorphous calcium phosphate (ACP) nanomaterial prepared in Example 1 is shown; wherein (a) is a diagram of the bacterial solution; and (b) is a diagram after the ACP and the bacterial solution are co-cultured;

[0059] Fig. 9 These are pictures showing the antibacterial effect of amorphous calcium copper phosphate (ACCP) nanomaterials prepared in Comparative Example 2; wherein (a) is a picture of bacterial solution; and (b) is a picture after co-culturing ACCP and bacterial solution;

[0060] Fig.10 This is a morphology picture of the composite bone repair material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0061] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0062] The present invention provides a method for preparing a composite bone repair material, comprising the following steps:

[0063] Step 1) mixing the amorphous calcium copper phosphate nanomaterial with a solution of a substrate material to obtain a substrate / amorphous calcium copper phosphate composite material; wherein the substrate material is a polymer material;

[0064] The step is specifically as follows: adding the amorphous calcium copper phosphate nanomaterial to the solution of the base material and stirring at the same time; stirring to ensure that the amorphous calcium copper phosphate (ACCP) nanomaterial is uniformly dispersed in the solution of the base material. The stirring speed is 200-1000 rpm and the stirring time is 6-12 hours; preferably, the stirring speed is 400-500 rpm and the stirring time is 8-10 hours.

[0065] Step 2) preparing the substrate / amorphous calcium phosphate copper composite material into a composite bone repair material;

[0066] The step is specifically: melt extrusion 3D printing of the substrate / amorphous calcium phosphate copper composite material to obtain a composite bone repair material; wherein: the printing temperature is 100-200°C; the extrusion speed is 0.05-0.5mm / s; the moving speed of the print head is 3-10mm / s; preferably, the extrusion speed is 0.05-0.15mm / s; the moving speed of the print head is 6-8mm / s. In order to facilitate printing, in the mixing treatment step in step 1), the amorphous calcium phosphate copper nanomaterial is a ground material.

[0067] Based on the above method, calcium ions in amorphous calcium copper phosphate nanomaterials help promote bone tissue regeneration, and copper ions have significant antibacterial properties, so that the obtained composite bone repair material has both osteogenesis and antibacterial properties, thereby solving the problems of infection after implantation of existing clinical bone repair materials. The substrate / amorphous calcium copper phosphate composite material can also be heated and melted, and then molded into a composite bone repair material of a certain shape using a mold; this application uses a 3D printing method to customize personalized composite bones according to the specific conditions of the patient.

[0068] In step 1), the particle size of the obtained amorphous calcium copper phosphate nanomaterial is 20-100 nm, and the nanomaterial within this particle size range is easier to enter cells; the mass percentage of the Cu element in the amorphous calcium copper phosphate nanomaterial is 0.1-20%; the steps of preparing the amorphous calcium copper phosphate nanomaterial include:

[0069] Step S1) mixing a mixed solution A containing a calcium inorganic salt, a copper inorganic salt and polyacrylic acid with a mixed solution B containing a phosphate and polyacrylic acid to obtain an emulsion; wherein the calcium inorganic salt is calcium chloride; the copper inorganic salt is cupric chloride; and the phosphate is diammonium hydrogen phosphate;

[0070] The step is specifically as follows: dissolving CaCl2·2H2O and CuCl2·2H2O in deionized water, adding polyacrylic acid, and mixing evenly to obtain a mixed solution A; dissolving diammonium hydrogen phosphate and polyacrylic acid in deionized water, and adding ammonia water dropwise to adjust the pH value to 7-10 to obtain a mixed solution B; under stirring, adding the mixed solution A dropwise to the mixed solution B; wherein the dropping speed is 1-50mL / min, the stirring speed is 200-1000rpm, and the stirring time is 0.5-3h; preferably, the dropping speed is 20-25mL / min, the stirring time is 2-2.5h, and the stirring speed is 400-500rpm;

[0071] In mixed solution A, the concentration of calcium chloride is 10-100 g / L, the concentration of copper chloride is 0.1-2 g / L, and the concentration of polyacrylic acid is 0.5-5 g / L; in mixed solution B, the concentration of diammonium hydrogen phosphate is 1-25 g / L, and the concentration of polyacrylic acid is 0.5-5 g / L. The amorphous calcium copper phosphate nanomaterial is stabilized by using polyanionic polymer polyacrylic acid. Specifically, the composite anions in polyacrylic acid can combine with calcium ions and copper ions of the amorphous calcium copper phosphate nanomaterial to form a nano-network structure, inhibit the crystallization of the amorphous calcium copper phosphate, and ensure that the material remains in an amorphous state for a long time. The concentration of copper chloride in mixed solution A is 0.1-2 g / L, which can ensure that the mass percentage of Cu element in the amorphous calcium copper phosphate nanomaterial is 0.1-20%. If the amount of copper is too little, it will not have an antibacterial effect, but excessive copper will produce cytotoxicity. Therefore, it is very necessary to control the release amount of copper, and the release amount of copper needs to be controlled within a range that can effectively fight bacteria and ensure cell activity.

[0072] Among them, when the amorphous calcium copper phosphate nanomaterial is mixed with the solution of the base material, the mass fraction of the amorphous calcium copper phosphate nanomaterial is less than 30% (that is, ACCP / ACCP+PLCL is less than 30%), so that the filament can be printed better. If the ACCP powder content is too high, the printing temperature needs to be increased to produce filaments, but too high a temperature will also cause carbonization of polylactic acid.

[0073] Step S2) centrifuging the emulsion to obtain a precipitate; wherein the centrifugal speed is 5000-10000 rpm, and the centrifugal time is 3-15 min; preferably, the centrifugal speed is 7000-9000 rpm, and the centrifugal time is 4-6 min;

[0074] Step S3) post-treating the precipitate to obtain an amorphous calcium copper phosphate nanomaterial;

[0075] The specific step is: dialyzing and cleaning the precipitate and freeze-drying it in sequence to obtain amorphous calcium phosphate copper nanomaterials.

[0076] The solution of the base material is prepared by the following preparation method: a polymer material is dissolved in an organic solvent to obtain a solution of the base material; wherein the polymer material includes polylactic acid and polycaprolactone;

[0077] The step specifically comprises: adding polylactic acid (PLA) and polycaprolactone (PCL) into dichloromethane at a mass ratio of 0.1-1:1, and heating and stirring at the same time to obtain a base material (PLCL) solution; heating and stirring accelerate the dissolution of the polymer material and make the dissolution more uniform;

[0078] In the solution of the base material: the concentration of polylactic acid is 5-50g / L; the concentration of polycaprolactone is 50-100g / L; wherein, the set temperature (heating temperature) is 20-50°C, the stirring speed is 200-1000rpm, and the stirring time is 1-3h; preferably, the set temperature is 30-40°C, the stirring speed is 400-500rpm; the number average molecular weight of polycaprolactone is 80000-100000; the number average molecular weight of polylactic acid is 60000-80000. The mass ratio of polylactic acid (PLA) and polycaprolactone (PCL) is 0.1-1:1. If the proportion of polylactic acid is too high, the temperature will increase accordingly during extrusion, resulting in carbonization and blackening of polylactic acid. When the content of polycaprolactone is low, the mechanical properties (modulus, strength) of the obtained composite bone repair material are low.

[0079] After the step of mixing the amorphous calcium copper phosphate nanomaterial with the solution of the base material, a heating treatment is further included; specifically, the heating treatment is carried out in an oven to ensure that the organic solvent dichloromethane is evaporated cleanly. The heating treatment temperature is 40-60°C; preferably 45-55°C.

[0080] The base material is a blend of polylactic acid (PLA) and polycaprolactone (PCL), which has the flexibility of polycaprolactone (PCL) and the mechanical strength of polylactic acid (PLA), providing good mechanical properties and biodegradability for the composite bone repair material. The base / amorphous calcium phosphate copper composite (PLCL) material obtained based on the polylactic acid (PLA) and polycaprolactone (PCL) of the present application, and the mass ratio (0.1-1:1) is subjected to melt extrusion 3D printing at a printing temperature of 100-200°C. If it is lower than 100°C, the PLCL material cannot reach a molten state and cannot be successfully extruded for subsequent printing; if it is higher than 200°C, the PLCL material will be carbonized during the extrusion process, the surface will become black, the filament will become brittle, and it cannot be formed into the required structure.

[0081] On the other hand, the present invention provides a composite bone repair material obtained by any of the above-mentioned preparation methods; the composite bone repair material comprises a base material and an amorphous calcium phosphate copper nanomaterial loaded on the base material, and the elastic modulus thereof is above 90 MPa and the yield strength is above 8 MPa.

[0082] The present invention is further described below in conjunction with specific examples and comparative examples. The main raw materials used are: CaCl2·2H2O (analytical grade), CuCl2·2H2O (analytical grade), ammonium phosphate (NH4)2HPO4 (analytical grade), ammonia NH3·H2O (analytical grade), and CH2Cl2 (analytical grade).

[0083] Example 1

[0084] This embodiment provides a method for preparing a composite bone repair material, comprising the following steps:

[0085] Step 1):

[0086] The method for preparing amorphous copper calcium phosphate nanomaterial comprises the following steps:

[0087] Step S1): 13.97g CaCl2·2H2O and 0.86g CuCl2·2H2O are dissolved in 500mL deionized water, and 0.5g polyacrylic acid is added and mixed uniformly to obtain a mixed solution A; 8.8g diammonium hydrogen phosphate and 6.0g polyacrylic acid are dissolved in 2L deionized water, and 25wt.% ammonia water is added dropwise to adjust the pH value to 9.2 to obtain a mixed solution B; under stirring, the mixed solution A is added dropwise to the mixed solution B at a speed of 20mL / min; wherein the stirring speed is 500rpm; and the stirring time is 2h;

[0088] In mixed solution A, the concentration of calcium chloride is 21.09 g / L, the concentration of copper chloride is 1.35 g / L, and the concentration of polyacrylic acid is 1 g / L; in mixed solution B, the concentration of diammonium hydrogen phosphate is 4.4 g / L, and the concentration of polyacrylic acid is 3 g / L;

[0089] Step S2): centrifuging the emulsion at 5000 rpm for 5 min to obtain a precipitate;

[0090] Step S3): the precipitate is dialyzed and washed for 48 hours, and then freeze-dried to obtain an amorphous calcium phosphate copper nanomaterial; wherein the mass percentage of the Cu element is 3.0wt.%; and the particle size of the amorphous calcium phosphate copper nanomaterial is 20-100nm;

[0091] Preparation of a solution of a base material: 4 g of polylactic acid (PLA) and 6 g of polycaprolactone (PCL) (mass ratio 0.67:1) were added to 100 mL of dichloromethane, and stirred at 500 rpm for 2 h at a temperature of 40° C. to obtain a base material (PLCL) solution;

[0092] Wherein: the number average molecular weight of polycaprolactone is 80,000; the number average molecular weight of polylactic acid is 80,000; in the solution of the base material: the concentration of polylactic acid is 40 g / L; the concentration of polycaprolactone is 60 g / L.

[0093] 2.5 g of the above-mentioned amorphous calcium copper phosphate nanomaterial was ground and added to the solution of the substrate material, and stirred at 500 rpm for 10 hours, and then placed in an oven and heated at 50° C. to evaporate the organic solvent dichloromethane to obtain a PLCL / ACCP composite material (substrate / amorphous calcium copper phosphate composite material).

[0094] Step 2): Use melt extrusion 3D printing to print the above-mentioned substrate / amorphous calcium phosphate copper composite material into a cylindrical structure with a diameter of 8 mm and a height of 8 mm, that is, a composite bone repair material; the parameters during the printing process are: printing temperature is 190°C, filling spacing is 1mm, filling rotation angle is 90°, number of rotations is 2 times, the aperture of the print head is 0.4mm; extrusion speed is 0.1mm / s; the movement speed of the print head is 7mm / s.

[0095] The morphology of the composite bone repair material obtained in this example is shown in Figure 4 As shown in (a), it can be seen that the scaffold has a good morphology.

[0096] Example 2

[0097] This embodiment provides a method for preparing a composite bone repair material, comprising the following steps:

[0098] Step 1):

[0099] The method for preparing amorphous copper calcium phosphate nanomaterial comprises the following steps:

[0100] Step S1): 13.97g CaCl2·2H2O and 0.86g CuCl2·2H2O are dissolved in 500mL deionized water, and 0.5g polyacrylic acid is added and mixed uniformly to obtain a mixed solution A; 8.8g diammonium hydrogen phosphate and 6.0g polyacrylic acid are dissolved in 2L deionized water, and 25wt.% ammonia water is added dropwise to adjust the pH value to 9.2 to obtain a mixed solution B; under stirring, the mixed solution A is added dropwise to the mixed solution B at a speed of 20mL / min; wherein the stirring speed is 500rpm; and the stirring time is 2h;

[0101] In mixed solution A, the concentration of calcium chloride is 21.09 g / L, the concentration of copper chloride is 1.35 g / L, and the concentration of polyacrylic acid is 1 g / L; in mixed solution B, the concentration of diammonium hydrogen phosphate is 4.4 g / L, and the concentration of polyacrylic acid is 3 g / L;

[0102] Step S2): centrifuging the emulsion at 5000 rpm for 5 min to obtain a precipitate;

[0103] Step S3): the precipitate is dialyzed and washed for 48 hours, and then freeze-dried to obtain an amorphous calcium phosphate copper nanomaterial; wherein the mass percentage of the Cu element is 3.0wt.%; and the particle size of the amorphous calcium phosphate copper nanomaterial is 20-100nm;

[0104] Preparation of a solution of a base material: 3 g of polylactic acid (PLA) and 7 g of polycaprolactone (PCL) (mass ratio 0.43:1) were added to 100 mL of dichloromethane, and stirred at 500 rpm for 2 h at a temperature of 40° C. to obtain a base material (PLCL) solution;

[0105] Wherein: the number average molecular weight of polycaprolactone is 80,000; the number average molecular weight of polylactic acid is 80,000; in the solution of the base material: the concentration of polylactic acid is 30 g / L; the concentration of polycaprolactone is 70 g / L.

[0106] 2.5 g of the above-mentioned amorphous calcium copper phosphate nanomaterial was ground and added to the solution of the substrate material, and stirred at 500 rpm for 10 hours, and then placed in an oven and heated at 50° C. to evaporate the organic solvent dichloromethane to obtain a PLCL / ACCP composite material (substrate / amorphous calcium copper phosphate composite material).

[0107] Step 2): Use melt extrusion 3D printing to print the above-mentioned substrate / amorphous calcium phosphate copper composite material into a cylindrical structure with a diameter of 8 mm and a height of 8 mm, that is, a composite bone repair material; the parameters during the printing process are: printing temperature is 170°C, filling spacing is 1mm, filling rotation angle is 90°, number of rotations is 2 times, the aperture of the print head is 0.4mm; extrusion speed is 0.1mm / s; the movement speed of the print head is 7mm / s.

[0108] The morphology of the composite bone repair material obtained in this example is shown in Figure 4 As shown in (b), it can be seen that the scaffold has a good morphology.

[0109] Example 3

[0110] This embodiment provides a method for preparing a composite bone repair material, comprising the following steps:

[0111] Step 1):

[0112] The method for preparing amorphous copper calcium phosphate nanomaterial comprises the following steps:

[0113] Step S1) 13.97g CaCl2·2H2O and 0.86g CuCl2·2H2O are dissolved in 500mL deionized water, and 0.5g polyacrylic acid is added and mixed uniformly to obtain a mixed solution A; 8.8g diammonium hydrogen phosphate and 6.0g polyacrylic acid are dissolved in 2L deionized water, and 25wt.% ammonia water is added dropwise to adjust the pH value to 9.2 to obtain a mixed solution B; under stirring, the mixed solution A is added dropwise to the mixed solution B at a speed of 20mL / min; wherein the stirring speed is 500rpm; and the stirring time is 2h;

[0114] In mixed solution A, the concentration of calcium chloride is 21.09 g / L, the concentration of copper chloride is 1.35 g / L, and the concentration of polyacrylic acid is 1 g / L; in mixed solution B, the concentration of diammonium hydrogen phosphate is 4.4 g / L, and the concentration of polyacrylic acid is 3 g / L;

[0115] Step S2): centrifuging the emulsion at 5000 rpm for 5 min to obtain a precipitate;

[0116] Step S3): the precipitate is dialyzed and washed for 48 hours, and then freeze-dried to obtain an amorphous calcium phosphate copper nanomaterial; wherein the mass percentage of the Cu element is 3.0wt.%; and the particle size of the amorphous calcium phosphate copper nanomaterial is 20-100nm;

[0117] Preparation of a solution of a base material: 2 g of polylactic acid (PLA) and 8 g of polycaprolactone (PCL) (mass ratio 0.25:1) were added to 100 mL of dichloromethane, and stirred at 500 rpm for 2 h at a temperature of 40° C. to obtain a base material (PLCL) solution;

[0118] Wherein: the number average molecular weight of polycaprolactone is 80,000; the number average molecular weight of polylactic acid is 80,000; in the solution of the base material: the concentration of polylactic acid is 20 g / L; the concentration of polycaprolactone is 80 g / L.

[0119] 2.5 g of the above-mentioned amorphous calcium copper phosphate nanomaterial was ground and added to the solution of the substrate material, and stirred at 500 rpm for 10 hours, and then placed in an oven and heated at 50° C. to evaporate the organic solvent dichloromethane to obtain a PLCL / ACCP composite material (substrate / amorphous calcium copper phosphate composite material).

[0120] Step 2): Use melt extrusion 3D printing to print the above-mentioned substrate / amorphous calcium phosphate copper composite material into a cylindrical structure with a diameter of 8 mm and a height of 8 mm, that is, a composite bone repair material; the parameters during the printing process are: printing temperature is 145°C, filling spacing is 1mm, filling rotation angle is 90°, number of rotations is 2 times, the aperture of the print head is 0.4mm; extrusion speed is 0.1mm / s; the movement speed of the print head is 7mm / s.

[0121] The morphology of the composite bone repair material obtained in this example is shown in Figure 4 As shown in (c), it can be seen that the scaffold has a good morphology.

[0122] Example 4

[0123] This embodiment provides a method for preparing a composite bone repair material, comprising the following steps:

[0124] Step 1):

[0125] The method for preparing amorphous copper calcium phosphate nanomaterial comprises the following steps:

[0126] Step S1): 13.97g CaCl2·2H2O and 0.86g CuCl2·2H2O are dissolved in 500mL deionized water, and 0.5g polyacrylic acid is added and mixed uniformly to obtain a mixed solution A; 8.8g diammonium hydrogen phosphate and 6.0g polyacrylic acid are dissolved in 2L deionized water, and 25wt.% ammonia water is added dropwise to adjust the pH value to 9.2 to obtain a mixed solution B; under stirring, the mixed solution A is added dropwise to the mixed solution B at a speed of 20mL / min; wherein the stirring speed is 500rpm; and the stirring time is 2h;

[0127] In mixed solution A, the concentration of calcium chloride is 21.09 g / L, the concentration of copper chloride is 1.35 g / L, and the concentration of polyacrylic acid is 1 g / L; in mixed solution B, the concentration of diammonium hydrogen phosphate is 4.4 g / L, and the concentration of polyacrylic acid is 3 g / L;

[0128] Step S2): centrifuging the emulsion at 5000 rpm for 5 min to obtain a precipitate;

[0129] Step S3): the precipitate is dialyzed and washed for 48 hours, and then freeze-dried to obtain an amorphous calcium phosphate copper nanomaterial; wherein the mass percentage of the Cu element is 3.0wt.%; and the particle size of the amorphous calcium phosphate copper nanomaterial is 20-100nm;

[0130] Preparation of a solution of a base material: 4 g of polylactic acid (PLA) and 6 g of polycaprolactone (PCL) (mass ratio 0.67:1) were added to 100 mL of dichloromethane, and stirred at 500 rpm for 2 h at a temperature of 40° C. to obtain a base material (PLCL) solution;

[0131] Wherein: the number average molecular weight of polycaprolactone is 80,000; the number average molecular weight of polylactic acid is 80,000; in the solution of the base material: the concentration of polylactic acid is 40 g / L; the concentration of polycaprolactone is 60 g / L.

[0132] 2.5 g of the above-mentioned amorphous calcium copper phosphate nanomaterial was ground and added to the solution of the substrate material, and stirred at 500 rpm for 10 hours, and then placed in an oven and heated at 50° C. to evaporate the organic solvent dichloromethane to obtain a PLCL / ACCP composite material (substrate / amorphous calcium copper phosphate composite material).

[0133] Step 2): Use melt extrusion 3D printing to print the above-mentioned substrate / amorphous calcium phosphate copper composite material into a cylindrical structure with a diameter of 8 mm and a height of 8 mm, that is, a composite bone repair material; the parameters during the printing process are: printing temperature is 190°C, filling spacing is 1mm, filling rotation angle is 60°, number of rotations is 3 times, the aperture of the print head is 0.4mm; extrusion speed is 0.1mm / s; the movement speed of the print head is 7mm / s.

[0134] The morphology of the composite bone repair material obtained in this example is shown in Figure 5 As shown in FIG. 1 , it can be seen that the scaffold has a good morphology. The SEM-EDS image of the composite bone repair material prepared in this embodiment is as follows: Figure 6 As shown, (a) is a surface morphology image under an electron microscope, from which it can be seen that the wires of the stent are uniform and the wire diameter is about 500 μm. Figure 6 Figures (b) to (d) are the distribution diagrams of Cu, Ca, P, C, and O elements, respectively. It can be seen that the main elements in the printed silk are evenly distributed, which shows that the printability and printing effect of the scaffold are good.

[0135] Example 5

[0136] This embodiment provides a method for preparing a composite bone repair material, comprising the following steps:

[0137] Step 1):

[0138] The method for preparing amorphous copper calcium phosphate nanomaterial comprises the following steps:

[0139] Step S1): 13.97g CaCl2·2H2O and 0.86g CuCl2·2H2O are dissolved in 500mL deionized water, and 0.5g polyacrylic acid is added and mixed uniformly to obtain a mixed solution A; 8.8g diammonium hydrogen phosphate and 6.0g polyacrylic acid are dissolved in 2L deionized water, and 25wt.% ammonia water is added dropwise to adjust the pH value to 9.2 to obtain a mixed solution B; under stirring, the mixed solution A is added dropwise to the mixed solution B at a speed of 20mL / min; wherein the stirring speed is 500rpm; and the stirring time is 2h;

[0140] In mixed solution A, the concentration of calcium chloride is 21.09 g / L, the concentration of copper chloride is 1.35 g / L, and the concentration of polyacrylic acid is 1 g / L; in mixed solution B, the concentration of diammonium hydrogen phosphate is 4.4 g / L, and the concentration of polyacrylic acid is 3 g / L;

[0141] Step S2): centrifuging the emulsion at 5000 rpm for 5 min to obtain a precipitate;

[0142] Step S3): the precipitate is dialyzed and washed for 48 hours, and then freeze-dried to obtain an amorphous calcium phosphate copper nanomaterial; wherein the mass percentage of the Cu element is 3.0wt.%; and the particle size of the amorphous calcium phosphate copper nanomaterial is 20-100nm;

[0143] Preparation of a solution of a base material: 4 g of polylactic acid (PLA) and 6 g of polycaprolactone (PCL) (mass ratio 0.67:1) were added to 100 mL of dichloromethane, and stirred at 500 rpm for 2 h at a temperature of 40° C. to obtain a base material (PLCL) solution;

[0144] Wherein: the number average molecular weight of polycaprolactone is 80,000; the number average molecular weight of polylactic acid is 80,000; in the solution of the base material: the concentration of polylactic acid is 40 g / L; the concentration of polycaprolactone is 60 g / L.

[0145] 2.5 g of the above-mentioned amorphous calcium copper phosphate nanomaterial was ground and added to the solution of the substrate material, and stirred at 500 rpm for 10 hours, and then placed in an oven and heated at 50° C. to evaporate the organic solvent dichloromethane to obtain a PLCL / ACCP composite material (substrate / amorphous calcium copper phosphate composite material).

[0146] Step 2): Use melt extrusion 3D printing to print the substrate / amorphous calcium phosphate copper composite material into a European collage structure formed by dense paving of triangles and quadrilaterals, that is, a composite bone repair material; the parameters during the printing process are: printing temperature is 185°C, filling spacing is 1mm, filling rotation angle is 90°, number of rotations is 2 times, the aperture of the print head is 0.4mm; extrusion speed is 0.1mm / s; the movement speed of the print head is 7mm / s.

[0147] The morphology of the composite bone repair material obtained in this example is shown in Figure 7 As shown, it can be seen that the scaffold has a good morphology. It can also be seen that composite bone scaffolds with different structures can be obtained through 3D printing.

[0148] The elastic modulus and compressive strength of the composite bone repair materials of Examples 1-3 were tested according to the method in GB / T 1041-2008. The test results are shown in the table below.

[0149] Elastic modulus (MPa) Yield strength(MPa) Example 1 118.12±5.35 10.55±0.74 Example 2 100.11±1.60 9.83±0.09 Example 3 93.54±2.02 8.54±0.24

[0150] It can be seen from the above table that the composite bone repair material obtained in the embodiment of the present invention has high elastic modulus and compressive strength, which can meet the needs of clinical application.

[0151] Example 6

[0152] The present embodiment provides a method for preparing an amorphous copper calcium phosphate nanomaterial, comprising the following steps:

[0153] Step S1): 14.41g CaCl2·2H2O and 0.34g CuCl2·2H2O are dissolved in 500mL deionized water, and 0.5g polyacrylic acid is added and mixed uniformly to obtain a mixed solution A; 8.8g diammonium hydrogen phosphate and 6.0g polyacrylic acid are dissolved in 2L deionized water, and 25wt.% ammonia water is added dropwise to adjust the pH value to 9.2 to obtain a mixed solution B; under stirring, the mixed solution A is added dropwise to the mixed solution B at a speed of 20mL / min; wherein the stirring speed is 500rpm; and the stirring time is 2h;

[0154] In mixed solution A, the concentration of calcium chloride is 21.76 g / L, the concentration of copper chloride is 0.54 g / L, and the concentration of polyacrylic acid is 1 g / L; in mixed solution B, the concentration of diammonium hydrogen phosphate is 4.4 g / L, and the concentration of polyacrylic acid is 3 g / L;

[0155] Step S2): centrifuging the emulsion at 5000 rpm for 5 min to obtain a precipitate;

[0156] Step S3): The precipitate is dialyzed and cleaned for 48 hours, and then freeze-dried to obtain an amorphous calcium phosphate copper nanomaterial; wherein the mass percentage of the Cu element is 1.2wt.%; and the particle size of the amorphous calcium phosphate copper nanomaterial is 20-100nm.

[0157] The amorphous calcium copper phosphate nanomaterial (ACCP) obtained in Example 6 and Example 1 was subjected to XRD analysis, and the spectrum is as follows: Figure 1 As shown, Example 6 and Example 1 correspond to Figure 1 The red and black lines in the middle; no sharp peaks are seen in the XRD pattern, indicating that the nanomaterial in the embodiment is an amorphous material. The ion release effect in the PBS simulated body fluid at pH = 5 is shown in FIG. Figure 2 As shown, it can be seen that the Ca and Cu ion contents released by ACCP dissolution correspond to the doping amount, and the ratio of Cu dissolution concentration to Ca dissolution concentration is constant, about 0.06, which is close to the theoretically calculated Cu to Ca mass ratio (0.08), and increases with the release concentration over time. In order to verify the antibacterial properties of the amorphous calcium copper phosphate nanomaterial (ACCP) obtained in the embodiment of the present invention, Staphylococcus aureus was co-cultured with the amorphous calcium copper phosphate nanomaterial obtained in Example 1, and the antibacterial rate was calculated with reference to GB31402-2015. The antibacterial rate of Staphylococcus aureus was >99%, indicating that the ACCP obtained in this embodiment has a good antibacterial effect. The bacterial solution is as follows: Figure 3 (a) and (b) show the results after co-culture. Figure 3 As shown in (c)-(f) , it can be seen that no colonies were formed.

[0158] Comparative Example 1

[0159] This comparative example provides a method for preparing a composite bone repair material, comprising the following steps:

[0160] Step 1)

[0161] The preparation of amorphous calcium phosphate nanomaterials comprises the following steps:

[0162] Step S1) 14.7g of CaCl2·2H2O was dissolved in 500mL of deionized water, and 0.5g of polyacrylic acid was added and mixed uniformly to obtain a mixed solution A; 8.8g of diammonium hydrogen phosphate and 6.0g of polyacrylic acid were dissolved in 2L of deionized water, and 25wt.% of ammonia water was added dropwise to adjust the pH value to 9.2 to obtain a mixed solution B; under stirring, the mixed solution A was added dropwise to the mixed solution B at a speed of 20mL / min; wherein the stirring speed was 500rpm; and the stirring time was 2h;

[0163] In mixed solution A, the concentration of calcium chloride is 22.2 g / L, and the concentration of polyacrylic acid is 1 g / L; in mixed solution B, the concentration of diammonium hydrogen phosphate is 4.4 g / L, and the concentration of polyacrylic acid is 3 g / L;

[0164] Step S2) centrifuging the emulsion at 5000 rpm for 5 min to obtain a precipitate;

[0165] Step S3) dialyzing and washing the precipitate for 48 hours, and then freeze-drying to obtain an amorphous calcium phosphate nanomaterial; the particle size of the amorphous calcium phosphate nanomaterial is 20-100 nm;

[0166] Preparation of a solution of a base material: 4 g of polylactic acid (PLA) and 6 g of polycaprolactone (PCL) (mass ratio 0.67:1) were added to 100 mL of dichloromethane, and stirred at 500 rpm for 2 h at a temperature of 40° C. to obtain a base material (PLCL) solution;

[0167] Wherein: the number average molecular weight of polycaprolactone is 80,000; the number average molecular weight of polylactic acid is 80,000; in the solution of the base material: the concentration of polylactic acid is 40 g / L; the concentration of polycaprolactone is 60 g / L.

[0168] 2.5 g of the above-mentioned amorphous calcium phosphate nanomaterial was ground and added to the solution of the substrate material, and stirred at 500 rpm for 10 h. It was then placed in an oven and heated at 50° C. to evaporate the organic solvent dichloromethane to obtain a PLCL / ACCP composite material (substrate / amorphous calcium phosphate composite material).

[0169] Step 2) Use melt extrusion 3D printing to print the above-mentioned substrate / amorphous calcium phosphate composite material into a cylindrical structure with a diameter of 8 mm and a height of 8 mm, that is, a composite bone repair material; the parameters during the printing process are: printing temperature is 190°C, filling spacing is 1mm, filling rotation angle is 90°, number of rotations is 2 times, the aperture of the print head is 0.4mm; extrusion speed is 0.1mm / s; the movement speed of the print head is 7mm / s.

[0170] The composite bone repair material obtained in this comparative example is obtained by 3D-forming a substrate / amorphous calcium phosphate composite material, and Staphylococcus aureus is co-cultured with the amorphous calcium phosphate nanomaterial obtained in comparative example 1, and its antibacterial effect is as follows: Figure 8 As shown, it can be seen that the number of colonies has not been significantly reduced, so the amorphous calcium phosphate nanomaterial in Comparative Example 1 does not have an antibacterial effect.

[0171] Comparative Example 2

[0172] This comparative example provides a method for preparing an amorphous calcium phosphate copper nanomaterial, comprising the following steps:

[0173] Step S1): 14.69g of CaCl2·2H2O and 0.01g of CuCl2·2H2O are dissolved in 500mL of deionized water, and 0.5g of polyacrylic acid is added and mixed uniformly to obtain a mixed solution A; 8.8g of diammonium hydrogen phosphate and 6.0g of polyacrylic acid are dissolved in 2L of deionized water, and 25wt.% of ammonia water is added dropwise to adjust the pH value to 9.2 to obtain a mixed solution B; under stirring, the mixed solution A is added dropwise to the mixed solution B at a speed of 20mL / min; wherein the stirring speed is 500rpm; and the stirring time is 2h;

[0174] In mixed solution A, the concentration of calcium chloride is 22.18 g / L, the concentration of copper chloride is 0.02 g / L, and the concentration of polyacrylic acid is 1 g / L; in mixed solution B, the concentration of diammonium hydrogen phosphate is 4.4 g / L, and the concentration of polyacrylic acid is 3 g / L;

[0175] Step S2): centrifuging the emulsion at 5000 rpm for 5 min to obtain a precipitate;

[0176] Step S3): The precipitate is dialyzed and cleaned for 48 hours, and then freeze-dried to obtain an amorphous calcium phosphate copper nanomaterial; wherein the mass percentage of the Cu element is 0.05wt.%; and the particle size of the amorphous calcium phosphate copper nanomaterial is 20-100nm.

[0177] In order to verify the antibacterial properties of the amorphous calcium copper phosphate nanomaterial (ACCP) obtained in the comparative example of the present invention, Fig. 9As shown, it can be seen that when Staphylococcus aureus is co-cultured with the amorphous calcium copper phosphate nanomaterial obtained in Comparative Example 2, the colony is not significantly reduced. Therefore, when the mass percentage of Cu element in the amorphous calcium copper phosphate nanomaterial is less than 0.1%, its antibacterial effect is poor.

[0178] Comparative Example 3

[0179] This comparative example provides a method for preparing a composite bone repair material, comprising the following steps:

[0180] Step 1):

[0181] The method for preparing amorphous copper calcium phosphate nanomaterial comprises the following steps:

[0182] Step S1): 13.97g CaCl2·2H2O and 0.86g CuCl2·2H2O are dissolved in 500mL deionized water, and 0.5g polyacrylic acid is added and mixed uniformly to obtain a mixed solution A; 8.8g diammonium hydrogen phosphate and 6.0g polyacrylic acid are dissolved in 2L deionized water, and 25wt.% ammonia water is added dropwise to adjust the pH value to 9.2 to obtain a mixed solution B; under stirring, the mixed solution A is added dropwise to the mixed solution B at a speed of 20mL / min; wherein the stirring speed is 500rpm; and the stirring time is 2h;

[0183] In mixed solution A, the concentration of calcium chloride is 21.09 g / L, the concentration of copper chloride is 1.35 g / L, and the concentration of polyacrylic acid is 1 g / L; in mixed solution B, the concentration of diammonium hydrogen phosphate is 4.4 g / L, and the concentration of polyacrylic acid is 3 g / L;

[0184] Step S2): centrifuging the emulsion at 5000 rpm for 5 min to obtain a precipitate;

[0185] Step S3): the precipitate is dialyzed and washed for 48 hours, and then freeze-dried to obtain an amorphous calcium phosphate copper nanomaterial; wherein the mass percentage of the Cu element is 3.0wt.%; and the particle size of the amorphous calcium phosphate copper nanomaterial is 20-100nm;

[0186] Preparation of a solution of a base material: 4 g of polylactic acid (PLA) and 6 g of polycaprolactone (PCL) (mass ratio 0.67:1) were added to 100 mL of dichloromethane, and stirred at 500 rpm for 2 h at a temperature of 40° C. to obtain a base material (PLCL) solution;

[0187] Wherein: the number average molecular weight of polycaprolactone is 80,000; the number average molecular weight of polylactic acid is 80,000; in the solution of the base material: the concentration of polylactic acid is 40 g / L; the concentration of polycaprolactone is 60 g / L.

[0188] 4.3 g of the above-mentioned amorphous calcium copper phosphate nanomaterial was ground and added to the solution of the substrate material, and stirred at 500 rpm for 10 hours, and then placed in an oven and heated at 50° C. to evaporate the organic solvent dichloromethane to obtain a PLCL / ACCP composite material (substrate / amorphous calcium copper phosphate composite material).

[0189] Step 2): The substrate / amorphous calcium phosphate copper composite material is printed into filaments by melt extrusion 3D printing; the parameters in the printing process are: printing temperature is 240° C., the aperture of the print head is 1.5 mm; and the extrusion speed is 1 mm / s.

[0190] The surface of the substrate / amorphous calcium phosphate copper composite material obtained in this comparative example is black, and the filaments are uneven and discontinuous. Fig.10 As shown, this is because polylactic acid is carbonized at high temperature and cannot be used for subsequent bone repair material preparation.

[0191] It is easy for those skilled in the art to understand that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.

[0192] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present invention. These improvements and variations should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a composite bone repair material, characterized in that: The following steps are involved: Step 1): mixing an amorphous calcium copper phosphate nanomaterial with a solution of a substrate material to obtain a substrate / amorphous calcium copper phosphate composite material; wherein the substrate material is a polymer material; Step 2): preparing the substrate / amorphous calcium phosphate copper composite material into a composite bone repair material.

2. The method for preparing the composite bone repair material according to claim 1, characterized in that: In the step 1): The particle size of the amorphous calcium copper phosphate nanomaterial is 20-100 nm; and / or The mass percentage of Cu element in the amorphous calcium phosphate copper nanomaterial is 0.1-20%.

3. The method for preparing the composite bone repair material according to claim 1 or 2, characterized in that: The preparation steps of the amorphous calcium copper phosphate nanomaterial include: Step S1): mixing a mixed solution A containing a calcium inorganic salt, a copper inorganic salt and polyacrylic acid with a mixed solution B containing a phosphate and polyacrylic acid to obtain an emulsion; Step S2): centrifuging the emulsion to obtain a precipitate; Step S3): post-treating the precipitate to obtain amorphous calcium copper phosphate nanomaterial.

4. The method for preparing the composite bone repair material according to claim 3, characterized in that: In the step S1): The calcium inorganic salt is calcium chloride dihydrate CaCl2·2H2O; the copper inorganic salt is copper chloride dihydrate CuCl2·2H2O; and / or The molecular weight of the polyacrylic acid is greater than 1000; and / or In the mixed solution A, the concentration of the calcium inorganic salt is 10-100 g / L, the concentration of the copper inorganic salt is 0.1-2 g / L, and the concentration of the polyacrylic acid is 0.5-5 g / L; and / or The phosphate is diammonium phosphate; and / or The mixed solution B is a mixed solution after the pH value is adjusted with aqueous ammonia; and / or The pH value of the mixed solution B is 7-10; and / or In the mixed solution B, the concentration of the phosphate is 1-25 g / L, and the concentration of the polyacrylic acid is 0.5-5 g / L; and / or The mixing treatment comprises: adding the mixed solution A dropwise to the mixed solution B under stirring; preferably, the dropping speed is 1-50 mL / min; more preferably, 20-25 mL / min; preferably, the stirring speed is 200-1000 rpm; more preferably, the stirring speed is 400-500 rpm; preferably, the stirring time is 0.5-3 h; more preferably, 2-2.5 h.

5. The method for preparing the composite bone repair material according to claim 3, characterized in that: In the step S2), the rotation speed of the centrifugal treatment is 5000-10000 rpm; preferably 7000-9000 rpm; and / or In the step S2), the centrifugal treatment time is 3-15 min, preferably 4-6 min; and / or In the step S3), the post-treatment step includes: washing and drying the precipitate in sequence; preferably, the washing method is dialysis washing; preferably, the drying method is freeze drying.

6. The method for preparing the composite bone repair material according to claim 1, characterized in that: In the step 1), the solution of the base material is prepared by the following preparation method: Dissolving a polymer material in an organic solvent to obtain a solution of the base material; wherein the polymer material comprises polylactic acid and polycaprolactone; and / or When the amorphous calcium copper phosphate nano material is mixed with a solution of a base material, the mass fraction of the amorphous calcium copper phosphate nano material is less than 30%.

7. The method for preparing the composite bone repair material according to claim 6, characterized in that: In the solution of the base material: the concentration of polylactic acid is 5-50 g / L; the concentration of polycaprolactone is 50-100 g / L; and / or Dissolving the polymer material in the organic solvent comprises: adding the polymer material to the organic solvent at a set temperature and stirring at the same time; preferably, the set temperature is 20-50°C; more preferably, the set temperature is 30-40°C; preferably, the stirring speed is 200-1000rpm; more preferably, the stirring speed is 400-500rpm; preferably, the stirring time is 1-3h; and / or In the polymer material, the mass ratio of polylactic acid to polycaprolactone is 0.1-1:1; and / or The number average molecular weight of the polycaprolactone is 80,000-100,000; and / or The number average molecular weight of the polylactic acid is 60,000-80,000; and / or The organic solvent is dichloromethane.

8. The method for preparing the composite bone repair material according to claim 1, characterized in that: In the step 1): The mixing treatment comprises: adding the amorphous calcium copper phosphate nanomaterial into a solution of a base material and stirring at the same time; preferably, the stirring speed is 200-1000 rpm; further preferably, the stirring speed is 400-500 rpm; preferably, the stirring time is 6-12 hours; further preferably, the stirring time is 8-10 hours; and / or After the mixing process, a heating process is further included; preferably, the temperature of the heating process is 40-60°C; further preferably, the temperature of the heating process is 45-55°C.

9. The method for preparing the composite bone repair material according to claim 1, characterized in that: In the step 2), the step of preparing the substrate / amorphous calcium phosphate copper composite material into a composite bone repair material comprises: 3D printing the substrate / amorphous calcium phosphate copper composite material to obtain the composite bone repair material; Preferably, during the 3D printing process: the printing temperature is 100-200°C; the extrusion speed is 0.05-0.5 mm / s; the moving speed of the print head is 3-10 mm / s; Further preferably, the extrusion speed is 0.05-0.15 mm / s; and the moving speed of the print head is 6-8 mm / s.

10. A composite bone repair material, characterized in that: The composite bone repair material comprises a base material and an amorphous calcium phosphate copper nanomaterial loaded on the base material; The elastic modulus of the composite bone repair material is greater than 90 MPa; the yield strength of the composite bone repair material is greater than 8 MPa; Preferably, the composite bone repair material is obtained by the preparation method according to any one of claims 1-9.